2005
DOI: 10.1021/jp040512q
|View full text |Cite
|
Sign up to set email alerts
|

Substituent Effects in the Migration Step of the Baeyer−Villiger Rearrangement. A Theoretical Study

Abstract: Quantum mechanical calculations have been performed on the migration step of the Baeyer-Villiger (BV) rearrangements of some acetophenones, p-RC6H4COCH3 (R = CN, Cl, H, CH3, CH3O) with m-chloroperbenzoic acid. The energy barriers, charge distributions, and frontier molecular orbitals determined for the aryl migration step explain the effects of substituents on the reactivity of these ketones. A plot of the log of relative oxidation rates of the ketones versus their corresponding calculated energy barriers of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
29
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 41 publications
(93 reference statements)
5
29
0
Order By: Relevance
“…However, some studies have shown that the carbonyl addition can also be rate determining and can depend on the reaction conditions as well as the reactants. [3,[16][17][18] For the carbonyl addition step, there is still no consensus on whether the protonation of the carbonyl oxygen and the carbonyl addition occur in a stepwise or concerted manner. [19] Besides, there are some controversies with regards to the potential effect of the acid, which is generated as a byproduct during the reaction and may catalyze both steps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies have shown that the carbonyl addition can also be rate determining and can depend on the reaction conditions as well as the reactants. [3,[16][17][18] For the carbonyl addition step, there is still no consensus on whether the protonation of the carbonyl oxygen and the carbonyl addition occur in a stepwise or concerted manner. [19] Besides, there are some controversies with regards to the potential effect of the acid, which is generated as a byproduct during the reaction and may catalyze both steps.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies have investigated B-V reactions with peroxycarboxylic acids as oxidants. [17][18][19][20][21][22][23] Remarkably, even though calculations indicated that the reactions can be catalyzed by general acid catalysis, through hydrogen-bond formation, there are still some contradictory results in the mechanism elucidation with regards to the molecularity and the mode of activation. [21,23] For the mechanism elucidation of the B-V oxidation with hydrogen peroxide, only a few computational studies have been published.…”
Section: Introductionmentioning
confidence: 99%
“…Despite many experimental and theoretical investigations of the mechanism, two questions are still under debate: 1) whether the first or second step of the reaction is the rate‐determining step (RDS) and 2) what are the key factors influencing the migration ability of alkyl groups of the ketone?8–13 In the 1950s, a rate‐limiting, acid‐catalyzed migration mechanism was proposed by Hawthorne and Emmons8 and then proved by kinetic studies on a series of p ‐substituted acetophenones by Simamura and co‐workers 9. However, depending on the reaction conditions and the nature of reactants, a switch in mechanism from rate‐determining migration to rate‐determining addition could also be observed,10 which is supported by computational studies by Reyes et al 11ac. and Grein et al 12.…”
Section: Introductionmentioning
confidence: 84%
“…The parallel formation of exo-2-hydroxy-4-oxaadamantane (61) was also attributed to the double Criegee rearrangement. The study 33 has a definite mechanistic relation to the above mentioned processes of tetrahydrofuran (38) and tetrahydropyran (34) …”
Section: Scheme 10mentioning
confidence: 99%
“…This data is also in an agreement with ρ-value of the relative migration rates of substituted benzyl groups (ρ=−2.1) 14,15 for Criegee rearrangement, as well as with the theoretical calculations for the Baeyer-Villiger reaction. 38 Therefore, the reaction rate of ionic decomposition of peroxyesters should be increased with increasing number of oxygen atoms attached to the C 1 -atom of the peroxide molecule (Table 1). This analysis is rather important for consideration of the mechanism of the consecutive Criegee rearrangement.…”
Section: Scheme 19mentioning
confidence: 99%